Water Management in Thailand†. (10th January 2018) - Apipattanavis, Somkiat; Ketpratoom, Sitha; Kladkempetch, Pradab
Abstract: The government of Thailand is now promoting the Thailand 4.0 model to escape its middle‐income level trap. The model uses an innovative 'value‐based economy' for climbing up to the high‐income level. The three main elements of this are: (i) a knowledge‐based economy; (ii) an inclusive society with equitable access; (iii) sustainable development. At present, Thailand consumes 90.4% of its fresh water for agricultural activities, while upper‐middle‐ and high‐income countries consume only 67.8 and 40.8% respectively. Therefore, Thailand is now developing strategic plans for proper water management for the next 20 years. The plans take the following concerns into consideration: (i) the principle of a water basin integrated framework and sustainable water management; (ii) government policies and the national economic and social development plan; (iii) the United Nation's Sustainable Development Goals. The strategies are still under discussion and not yet finalized at this moment. However, the plans will certainly hold significant weight in government project funding in the next 20 years. All of the water‐related projects will be carried out with the plans as a guideline. Meanwhile, each project will maintain the concepts of culture, tradition, geography and demography to obtain the highest compatibility with Thai society. Copyright © 2018 John Wiley & Sons, Ltd.